2010
DOI: 10.1159/000319361
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and ABCB1 Gene C3435T Functional Polymorphism: A Naturalistic Study

Abstract: Introduction: Pharmacogenetic factors may explain some of the interindividual variability of response to antidepressants in depressed patients. We focused on P-glycoprotein (P-GP), whose expression depends on a functional polymorphism of the ABCB1 gene (C3435T variants: dbSNP: rs1045642), the 3435CC genotype being linked to a high level of P-GP expression. Acting as an efflux pump at the blood-brain barrier, P-GP reduces the intracellular penetration of many drugs. Little is known about the interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
4
16
2
Order By: Relevance
“…Consequently, various studies aimed at replicating this pharmacogenetic association with mixed results. A considerable body of research corroborated the finding by Uhr et al [] [Gex‐Fabry et al, ; Kato et al, ; Nikisch et al, ; Sarginson et al, ; Lin et al, ; Singh et al, ; Huang et al, ], but there were also a number of studies that failed to find a predictive value of ABCB1 polymorphisms on therapy outcome [Peters et al, ; Mihaljevic Peles et al, ; Menu et al, ; Perlis et al, ; Uher et al, ; GENDEP Investigators, MARS Investigators, and SI, ]. The possible reasons for these contradictory results are diverse and coincide with a generally observed difficulty in the replication of pharmacogenetic associations caused by, for example, heterogeneity of study designs and patient samples, variability in phenotype definitions (MD being a particularly heterogeneous phenotype), inadequate statistical power, environmental factors, and polymorphic heterogeneity, making it difficult to compare results across studies.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Consequently, various studies aimed at replicating this pharmacogenetic association with mixed results. A considerable body of research corroborated the finding by Uhr et al [] [Gex‐Fabry et al, ; Kato et al, ; Nikisch et al, ; Sarginson et al, ; Lin et al, ; Singh et al, ; Huang et al, ], but there were also a number of studies that failed to find a predictive value of ABCB1 polymorphisms on therapy outcome [Peters et al, ; Mihaljevic Peles et al, ; Menu et al, ; Perlis et al, ; Uher et al, ; GENDEP Investigators, MARS Investigators, and SI, ]. The possible reasons for these contradictory results are diverse and coincide with a generally observed difficulty in the replication of pharmacogenetic associations caused by, for example, heterogeneity of study designs and patient samples, variability in phenotype definitions (MD being a particularly heterogeneous phenotype), inadequate statistical power, environmental factors, and polymorphic heterogeneity, making it difficult to compare results across studies.…”
Section: Introductionmentioning
confidence: 66%
“…Association results from Roberts et al [], Gex‐Fabry et al [], Kato et al [], Mihaljevic Peles et al [], Nikisch et al [], Uhr et al [], Menu et al [], Sarginson et al [], Lin et al [], Singh et al [], and the STAR*D sample were combined in the meta‐analysis with a total of 1,845 patients (see Table ). We found no significant association between rs1045642 and P‐gp substrate treatment outcome, neither in the overall meta‐analysis nor after stratification for ethnicity, in‐/outpatient status or co‐medication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, genetic variations in P‐gp might affect the response to treatment, remission and side effects risk . Up to the present, although some research studies of major depressive disorder (MDD) and psychosis have shown an influence of ABCB1 polymorphisms in treatment outcome , in most cases, these results could not be replicated .…”
mentioning
confidence: 86%
“…This gene encodes the P-glycoprotein (P-gp), a plasma membrane transporter that has a critical role in the regulation of the blood-brain barrier transportation of many drugs, including antidepressants [24]. 2 polymorphisms, 1 non-synonymous SNP (G2677T or rs2032582) and 1 synonymous SNP (C3435T or rs1045642), have been associated with altered P-glycoprotein activity [25,26]. Animal studies have indicated that many antidepressants are significant P-gp substrates while others are not [27].…”
Section: Introduction ▼mentioning
confidence: 99%